Rapid pathogen identification using a novel microarray-based assay with purulent meningitis in cerebrospinal fluid. Issue 1 (December 2018) - Hou, Yuting; Zhang, Xu; Hou, Xiaolin; Wu, Ruofen; Wang, Yanbai; He, Xuexian; Wang, Libin; Wang, Zhenhai
Abstract In order to improve the diagnosis of pathogenic bacteria in cerebrospinal fluid (CSF) with purulent meningitis, we developed a DNA microarray technique for simultaneous detection and identification of seven target bacterium. DNA were extracted from 24 CSF samples with purulent meningitis (or suspected purulent meningitis). The specific genes of each pathogen were chosen as the amplification target, performed the polymerase chain reaction (PCR), labeled with a fluorescence dye, and hybridized to the oligonucleotide probes on the microarray. There is no significant cross-hybridization fluorescent signal occurred in untargeted bacteria. There were 87.5% (21/24) positive results in DNA microarray compared with the 58.3% (14/24) of the CSF culture test. Of which 58.3% (14/24) of the patients with culture-confirmed purulent meningitis, 37.5% (9/24) patients who were not confirmed by culture test but were demonstrated by the clinical diagnosis and DNA microarray. Multiple bacterial infections were detected in 5 cases by the microarray. In addition, the number of gene copies was carried out to determine the sensitivity of this technique, which was shown to be 3.5 × 101 copies/μL. The results revealed that the microarray technique which target pathogens of the CSF specimen is better specificity, accuracy, and sensitivity than traditional culture method. The microarray method is an effective tool for rapidly detecting more target pathogens and identifying the subtypes of strains which can eliminate the impact of the different individuals with purulent meningitis for prompt diagnosis and treatment.